Payleteerr Demi Gengsi - Ageng Kanda Saepudin S; Dela Apriliana (Pusat Riset dan Inovasi Nasional, 2025)
The use of Paylater as a means to achieve a desired lifestyle, especially among the younger generation, is the highlight of this research. With a focus on psychological and financial impacts, this study combines qualitative and quantitative approaches to investigate the complex interactions between demographic factors, motivations, and the consequences of using Paylater for prestige. Through data collection using questionnaires and interviews with samples covering various age groups, education levels, and income levels, the research results highlight interesting findings. The main motivation for using Paylater was revealed as a drive to achieve a prestigious image and keep up with emerging digital consumption trends. The psychological impact cannot be ignored either, with some respondents admitting to the financial stress associated with this habit. Data analysis shows that education level plays an important role in an individual's ability to manage Paylater debt. Respondents with a higher level of education tend to be more aware of risk and have better debt management strategies. The implications of the results of this research include challenges in financial literacy and psychological well-being in the digital era. A more targeted approach is needed to educate young people about the financial risks associated with using Paylater for prestige. Nonetheless, this study acknowledges limitations in the generalisability of the results and suggests further research to investigate alternative financial management strategies and the long-term impact of this phenomenon